Building the Ontario Surgical Oncology Program. Issue 1 (January 2018) - Sullivan, Terrence; Irish, Jonathan
From the 1940s onward the establishment of an increasing number of cancer centres in Ontario concentrated predominantly on radiation and systemic therapy. Increasing attention to the organization of cancer surgery services in Ontario over the last 3 decades through measures led by Cancer Care Ontario has resulted in building a progressive provincial and regional surgical oncology network. These networks are rooted in leadership mobilization and have used quality data and best evidence to promote the elaboration of communities of practice to achieve better outcomes. This article briefly chronicles this journey and points to areas of progress.